Fish Nematode Huffmanela spp. (Enoplea: Trichinellida: Trichosomoididae) - Jennifer Lynn Gillett-Kaufman; Fauve Wilson (EDIS)
Huffmanela is a genus of parasitic nematodes in the family Trichosomoididae. Huffmanela species infest only one freshwater fish species and a small number of saltwater fishes. They commonly affect many tissues in particular the swim bladder, gut mucosa, skin, and musculature (Carballo and Navone 2007). https://edis.ifas.ufl.edu/in1276